Divergence of ontogenetic dietary shifts in adaptive radiation - Grégoire Saboret; Coralie Moccetti; Soraya Lamochi Roozalipour; Carsten J. Schubert; Jakob Brodersen (Proceedings of the National Academy of Sciences, 2026)
The availability of trophic niches is a key driver of biodiversity, promoting adaptive radiation through evolutionary processes. However, most research has focused on how species adapt to trophic niches as adults, largely overlooking the fact that many taxa undergo significant ontogenetic dietary shifts. Here, we address this gap by investigating individual dietary shifts in an incipient adaptive radiation of Arctic charr ( Salvelinus alpinus ), where distinct piscivorous and planktivorous lacustrine morphs have diverged. Using eye lens isotopes, we reconstructed dietary histories at the individual level, tracing resource use from maternal nutrients to adult diet. Our analyses revealed three key dimensions in which ontogenetic dietary shifts diverge: early-life diets, the stability of dietary transitions, and the degree of plasticity in dietary shifts. These findings suggest that the early phases of adaptive radiation are accompanied by a complete divergence of ontogenetic dietary shifts. We advocate for a more integrated approach to understanding dietary shifts within evolutionary processes and call for further exploration of these patterns across diverse taxa.